Contemporary children’s literature, myth or reality? - Petrova, S.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Literaturovedenie, zhurnalistika, 2018)
The article justifies the obligatory and actuality school education of contemporary child’s book as a “key mediatext of culture”; revealed the reasons of the underestimation of child’s literature formed in society; describes the contemporary processes that go in child’s book business; proved the necessity of development informative politics elaborate at government level. The novelty of the research consists in the exposure of basic negative tendencies, that led Russia’s loss of status not only “the most reading country of the world” but also simply “reading country”, in the proposals by the author the concrete measures for the improvement of situation in area of reading and child’s national book industry. A scientific value presented the generalizations and conclusions, done by the author who based on the study of specific properties of contemporary child’s and teenage literature, in particular: its “ovzroslenie” - “written for children as for adults” - attraction to journalism, genres deflections, structural changes of texts, violation of logic narrative and composition and other.